The International Committee of the Red Cross: an Evaluation - Basaran, Halil Rahman (UI Scholars Hub, 2020)
The International Committee of the Red Cross (ICRC) is explicitly mentioned in the 1949 Geneva Conventions and the 1977 Additional Protocols thereto. These explicit references to the ICRC entail respect for and recognition of the ICRC as the oldest humanitarian institution. However, this explicitness does not imply, suggest or confirm legal superiority of the ICRC over other humanitarian institutions, nor does it make the ICRC the exclusive humanitarian organization. Humanitarian assistance can be legally and legitimately undertaken by other humanitarian organizations as well. The practical influence of the ICRC is greater than that of any other NGO. Arguably, the survival of the ICRC as the pre-eminent provider of humanitarian assistance is testimony to the fact that the “practicalities” of international law are as important as treaties. The practices of the undisputed subjects of international law – states and international organizations – have paved way for a half-subject of international law – the ICRC – to enhance its status.